Photodegradation of Direct Blue-199 in carpet industry wastewater using iron-doped TiO2 nanoparticles and regenerated photocatalyst - Saroj S.; Singh L.; Singh S.V. (My University, 2025)
Fe-doped TiO2, Ti1– xFexO2 (x = 0.00, 0.02, 0.04, 0.06, 0.08, and 0.10), photocatalysts have been successfully synthesized via citric acid–assisted autocombustion method. The synthesized photocatalysts were characterized using different characterization techniques, such as X-ray diffraction (XRD), diffuse reflectance spectroscopy (DRS), Fourier transform infrared (FT-IR), transmission electron microscopy (TEM), energy dispersive x-ray spectroscopy (EDX), and x-ray photoelectron spectroscopy (XPS). The XRD diffraction patterns revealed that synthesized photocatalysts have the anatase phase of TiO2. The DRS analysis indicates a slight increment in absorbance in the visible light region by the Fe doping in TiO2. The FT-IR spectra reveal the various stretching and bending vibrational bands of the Ti–O lattice. The XPS spectra confirm the presence of elements titanium, oxygen, and iron in the synthesized samples and determine binding energy of elements. TEM analysis shows the shape of the synthesized photocatalyst, and it was used to calculate the average particle sizes of undoped and Fe-doped TiO2 (Ti0.96Fe0.04O2) photocatalysts using a histogram. The photocatalytic activities of synthesized photocatalysts were determined by photodegradation of dye (Direct Blue 199), contaminating carpet industry wastewater in the photochemical reactor and open pan reactor. The maximum photodegradation activity was shown by the Ti0.96Fe0.04O2 photocatalyst among all the synthesized undoped and Fe-doped photocatalysts. The synthesized photocatalyst (Ti0.96Fe0.04O2) had better photocatalytic activity when compared to both, undoped TiO2 and Aeroxide (Degussa) P-25. The used Fe-doped TiO2 photocatalyst (Ti0.96Fe0.04O2) was regenerated five times and investigated for its photocatalytic activity. © 2018 Wiley Periodicals, Inc.